Pengaruh Pendapatan Asli Daerah dan Sisa Lebih Perhitungan Anggaran Terhadap Perilaku Oportunistik Penyusunan Anggaran di Provinsi Bengkulu Tahun 2013-2017 - Nina Yulianasari; Pedi Riswandi (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2021)
In this study, we have studied the influence of the regional budget component (Regional Income and Excess Budget Calculation) on opportunistic behavior in Bengkulu Province. The important problem with this research is the fact that the level of corruption in Bengkulu Province is relatively high. For 3 consecutive periods the governor of Bengkulu province was entangled in corruption cases, while on the other hand the poverty rate in Bengkulu province was among the highest in Sumatera. The data used was secondary data and primary data. The population and samples in this study were regional revenue and expenditure budget (APBD) throughout the District and City of Bengkulu Province during the research period of 2013-2017 and 22 respondents from the legislature and executive as the budgeting party. The methods used were qualitative and quantitative. The results of the t-test showed that the regional income (PAD) variable has a probability value of 0.0000. If seen from the significance of 0.0000 < 0.05, then Hypothesis 1 is accepted which means the regional income has an influence on the opportunistic behavior of budgeting in Bengkulu Province. The excess budget (SiLPA) obtains a probability of 0.0602 or greater than alpha 0.05, but smaller than alpha 0.10 at 90% confidence level. Thus, Hypothesis 2 is accepted which means that the excess budget (SiLPA) has an influence on the opportunistic behavior of budgeting in Bengkulu Province.